Childhood fever: a qualitative study on parents' expectations and experiences during general practice out-of-hours care consultations. Issue 1 (December 2015) - de Bont, Eefje; Loonen, Nicole; Hendrix, Dagmar; Lepot, Julie; Dinant, Geert-Jan; Cals, Jochen
Abstract Background Fever in children is common and mostly caused by benign self-limiting infections. Yet consultation rates in primary care are high, especially during GP out-of-hours care. Therefore, we aimed to explore experiences of parents when having visited GP out-of-hours services with their febrile child. Methods We performed a qualitative study using 20 semi-structured interviews among parents from different backgrounds presenting to GP out-of-hours care with a febrile child <12 years. Questions were directed at parental motivations, expectations and experiences when visiting the GP out-of-hours centre with a febrile child. Interviews were audio-recorded, transcribed and analysed using constant comparison technique. Results We identified four main categories emerging from the data; (1) cautiously seeking care, (2) discrepancy between rationality and emotion, (3) expecting reassurance from a professional and (4) a need for consistent, reliable information. Not one symptom, but a combination of fever with other symptoms, made parents anxious and drove care seeking. Although parents carefully considered when to seek care, they experienced increased anxiety with increases in their child's temperature. Because parents work during the day and fever typically rises during the early evening, the decision to seek care was often made during out-of-hours care. When parents consulted a GP they did not have any set expectations other than seeking reassurance, however a proper physical examination diminished their anxiety. Parents did not demand antibiotics, but trusted on the expertise of the GP to assess necessity. Parents requested consistent, reliable information on fever and self-management strategies. Conclusions Parents were inexperienced in self-management strategies and had a subsequent desire for reassurance; this played a pivotal role in out-of-hours help seeking for childhood fever. These factors provide clues to optimise information exchange between GPs and parents, by providing written, tailored, consistent information on self-management strategies for current and future fever episodes. GPs' had incorrect assumptions that parents expected antibiotic treatment.